Prospección y selección de aislados de Trichoderma spp. y Pochonia spp. para el control biológico del nematodo agallador de tomate en condiciones in vitro e invernadero - León Ochoa, Idalmis Romina (2019)
The gall-forming nematode (Meloidogyne incognita) is one of the most important pests that affect the tomato crop due to the losses caused annually. With the aim of reducing the levels of infestation of this pest in the tomato crop and provide environmentally friendly alternatives, in the laboratory of Plant Health and greenhouse of the agricultural area belonging to the National University of Loja, the present work was developed of thesis, evaluating the parasitic effect of native isolates of the genus Trichoderma and the genus Pochonia obtained from samples of soil and roots of tomato plants in producing areas of the province of Loja, which were evaluated for their biocontrol capacity in eggs and juveniles j2 of Meloidogyne incognita. Under in vitro conditions, the isolation and parasitic evaluation of 11 nematophagous isolates of the fungus Trichoderma spp. and 7 isolates of the genus Pochonia spp., in 3 conidial concentrations of 107, 108, 109. The evaluation of the bioassay for Trichoderma spp, allowed to select 4 isolates with a parasitism in eggs of 70 to 88.8% and in J2 larvae of 70% 81.3%; while the bioassay for Pochonia spp., 4 isolates were selected with parasitism in eggs from 70% to 90.8% and 14.7 to 50.3 in juveniles J2. The morphological characterization studies determined two Trichoderma species identified as Trichoderma harzianum and Trichoderma viride and two Pochonia species known as Pochonia chlamydosporia var. catenulata and Pochonia chlamydosporia var. chlamydosporia Under greenhouse conditions, the most effective parasitic isolates were evaluated in plants grown in polyethylene pots, inoculated with 3000 J2 of M. incognita and fungal spores of the isolates in 3 conidial concentrations of 108, 109, 1010 in two applications (2 days after the transplant and 40 days after the first inoculation), which affected the reduction of the gill index (Bridge and Page, 1980), reduction of J2 populations in soil and roots, as well as in the positive expression of the agronomic variables . Key words: Trichoderma spp., Pochonia spp., Nematode, Meloidogyne incognita, biocontrol, tomato.